2013
DOI: 10.1073/pnas.1308295110
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and biochemical dissociation of arousal and homeostatic sleep need influenced by prior wakeful experience in mice

Abstract: Sleep is regulated by homeostatic mechanisms, and the low-frequency power in the electroencephalogram (delta power) during nonrapid eye movement sleep reflects homeostatic sleep need. Additionally, sleep is limited by circadian and environmentally influenced arousal. Little is known, however, about the underlying neural substrates for sleep homeostasis and arousal and about the potential link between them. Here, we subjected C57BL/6 mice to 6 h of sleep deprivation using two different methods: gentle handling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(93 citation statements)
references
References 30 publications
3
85
1
Order By: Relevance
“…Mild sleep deprivation caused by a cage change34 during ZT4–6 for 3 consecutive days did not shift the phase of peripheral clocks (Figure S7A), indicating that sleep deprivation was not involved in stress-induced circadian entrainment. Stress-induced changes in feeding behaviour and body temperature can also lead to alterations in circadian rhythm353637383940.…”
Section: Resultsmentioning
confidence: 98%
“…Mild sleep deprivation caused by a cage change34 during ZT4–6 for 3 consecutive days did not shift the phase of peripheral clocks (Figure S7A), indicating that sleep deprivation was not involved in stress-induced circadian entrainment. Stress-induced changes in feeding behaviour and body temperature can also lead to alterations in circadian rhythm353637383940.…”
Section: Resultsmentioning
confidence: 98%
“…The subsequent discovery of Rapid Eye Movement (REM) and non-REM sleep [11] demonstrated that these different sleep states are generated by distinct physiological processes [12]. Experiments using the EEG have also revealed that slow wave activity can serve as a biomarker for sleep need in certain settings [13,14]. …”
Section: Behavioral and Electrophysiological Properties Of Sleepmentioning
confidence: 99%
“…Since sleep duration is primarily a function of arousal system activity, it appears that arousal and sleep homeostasis can be dissociated by disrupting the Ado system that links the two (6, 24). On the other hand, different experimental methods of sleep deprivation of the same duration, lead to different levels of arousal with relatively small effect on homeostatic SWA (27). One may, nonetheless speculate that waking activity that especially activates the LC, would elicit a stronger sleep homeostatic response based on the findings that depletion of NE reduces this same response (13).…”
Section: Mechanisms Controlling the Sleep Homeostatic Responsementioning
confidence: 99%
“…The method of sleep deprivation can determine the level of arousal. We have reported that sleep deprivation induced by cage change results in higher arousal than gentle handling (27). The panel of activity-activated gene expression varied in correlation with arousal level as elicited by either cage change or gentle handling.…”
Section: Functional Cns Targets Of the Homeostatic Sleep Responsementioning
confidence: 99%